Problems & Challenges Faced by working women in Bangalore City: A Study on Financial Planning - V, Mrs. Indumathi; S N, Mrs. Lakshmi (The journal of contemporary issues in business and government, 2023)
The present paper explores one of the most important aspects related to new dimensions where women are competing neck to neck with her male companions. Increase in women’s planning rates, their exposure to better educational and job opportunities and changing government policies towards women empowerment have enabled them to realize the importance of financial independence. Financial Planning is required for all men and women, irrespective of their age, educational background, income level, socio-cultural affiliation and family status. However, financial planning is considered mandatory for women, while it is important for men. Women outlive men by 2 to 3 years in India Women's contributions in the social and political sectors are expanding. Due to number of variables such as delayed marriageable age, rising divorce rates, women bearing greater financial responsibility for financially supporting children, and the growing requirement for two-income homes, the burden of financial stress is increasingly falling on women. Thus, women need to plan their finances at every stage of her life so that she is equipped to handle any contingency of their life alone. Therefore, women need to be financially literate and actively participate in all the financial planning so that, at the time of difficulty, she can manage the finances confidently. The purpose of the present paper is to identify various needs and factors affecting financial planning of women.